EKSPERIMEN FISIKA MODEL PEMBELAJARAN SCIENTIFIC INQUIRY TERHADAP KETERAMPILAN 4C SISWA DI SMAN 6 PADANGSIDIMPUAN - Siregar, Yenni Amalia; Siregar, Dedes Asriani (Jurnal Physics Education (PhysEdu), 2025)
The study aims to analyze the experiment of scientific inquiry learning model in improving students 4C skills (Collaboration, Communication, Critical Thinking and Creativity) for physics learning on static fluid material. The population of this study was all class XI students of SMAN 6 Padangsidimpuan in the 2025/2026 academic year. The sampling technique in the study used a cluster random class, the experimental class used the scientific inquiry learning model and the control class used conventional learning. The variables in the study consisted of 4C skills as the dependent variable and the scientific inquiry model as the independent variable. The data in this study were analyzed using a t-test. The results showed that students 4C skills with the scientific inquiry learning model were better than students 4C skills with conventional learning.